The Effectiveness of the Strategy (SCAMPER) to Generate Ideas in Learning the Skill of the Service is Facing from the Top and Down in the Volleyball for Students - Saeed Gheni Noori (Journal of Global Pharma Technology, 2016)
The study objective to identify the effectiveness of the (SCAMPER) strategy to generate ideas in learning the skills of the service is facing from the top and down in the volleyball, the experimental society was used, while the research society was identified by students in the fifth grade preparatory class (scientific and biological) for the Secondary School of Civilizations for Boys in Misan Governorate / Iraq for the academic year 2017-2018, which reached (64) students, and distribution into two groups, the control group's branch of biological (28) students applied the experimental branch's group (28) students either the rest of the students excluded from the sample for their participation experience reconnaissance. The parity of the two groups has been carried out in the accuracy of the skill of service is facing from the top, it has been applied (12) and the educational unit for both groups in accordance with the program unified distributed according to two units per week of educational duration of the unit per (45) minutes, researchers have concluded that the effectiveness of the program prepared in accordance with the strategy (SCAMPER) to generate ideas in learning the skills of the service is facing from the top and down in volleyball the experimental group, as well as students interact with the strategic development of creative thinking.Keywords: Strategy (SCAMPER) for generating ideas, Service is facing top and down in the volleyball.